All intra-regular generalized hypersubstitutions of type (2) - Ampika Boonmee (2019)
© 2019 Ampika Boonmee et al., published by Sciendo 2019. A generalized hypersubstitution of type τ maps each operation symbol of the type to a term of the type, and can be extended to a mapping defined on the set of all terms of this type. The set of all such generalized hypersubstitutions forms a monoid. An element a of a semigroup S is intra-regular if there is b S such that a = baab. In this paper, we determine the set of all intra-regular elements of this monoid for type τ = (2).